Решить уравнение: 6+(2-4x)+5=3(1-3x) 0,5(2y-1)-(0,5-0,2y)+1=0 0,15(x-4)=9,9-0,3(x-1) 3(3x-1)+2=5(1-2x)1

Решить уравнение: 6+(2-4x)+5=3(1-3x) 0,5(2y-1)-(0,5-0,2y)+1=0 0,15(x-4)=9,9-0,3(x-1) 3(3x-1)+2=5(1-2x)1
Гость
Ответ(ы) на вопрос:
Гость
  1) 6+(2-4х)+5=3(1-3х)   6+2-4х+5=3-9х -4х+9х=3-5-2-6 5х=-10 х=-2 2) 0,5(2у-1)-(0,5-0,2у)+1=0 1у-0,5-0,5+0,2у+1=0 1у-0,2у=0,5+0,5+1 0,8у=2 у=2,5 3) 0,15(х-40=9,9-0,3(х-1) 0,15х-0,6=9,9-0,3х+0,3 0,15х+0,3х=9,9+0,3+0,6 0,45х=10,8 х=2,4                                                                
Гость
6+2-4x+5=3-9x;   1y-0.5-0.5+0.2y+1=0;     0.15х+0.6=9.9-0.3x+0.3;           9х-3+2=5-10х; 10+5x=0;               1.2y=0;                              0.45х=10.2-0.6;                           19х=6; 5x=-10;                   y=0;                                    0.45х=9.6;                                     х=6/19 x=-2                                                                    х=21.(3)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы